Cost Analysis of Nursing Practice by Applying Reuse and Repack Methods on Sterile Practice Materials in the Clinical Laboratory - Henny Yulianita; Afif Amrullah; Dyah Setyorini (Universitas Padjadjaran, 2018)
The activity of nursing practice in the laboratory, required sterile equipment that is still wrapped neatly. Equipment had broken wrap, will be discarded. Although the equipment is still good and feasible to be reused. Reuse and repack is a method of repackaging of used sterile equipment.This method is expected to reduce the cost of practice and reduce environmental waste. This study aims to analyze the cost of nursing practice by applying reuse and repack methods on sterile practice materials. This study is a field study using observation method on the practice of urinary catheter insertion and nasogastric tube installation conducted by nursing students in the clinical laboratory. The number of students involved as many as 74 people. Instrument tool pricing standards based on online rates published by health equipment standard sites. Findings Through the application of reuse and repack methods, the cost of the practice of urinary catheter insertion can be saved by 1.6 million (90%) and the cost of installation practice can be saved by 3.6 million (85%) for once practice. The results of the cost analysis of nursing practice in the laboratory using reuse and repack methods on the practice of urinary catheter insertion and the practice of ngt installation can save the cost of nursing practice.